Efeito da técnica restauradora, do tipo de preparo e do envelhecimento de restaurações de resina composta sobre a resistência à fratura dental, resistência adesiva e vedamento marginal - Souza, Fábio Herrmann Coelho de (2006)
The aim of this study was to evaluate, in vitro, the effect of composite resin restoration techniques, bevel and storage time on the fracture strength, restoration retention and gap formation. For the fracture strength test, standard MOD cavities were prepared in 100 upper premolars, which were divided in two storage times (24 hours and 6 months with 1000 thermocycles), and in each group, sub-groups were randomly formed as follow: group 1 direct composite resin restoration(Filtek Z250 and Adper Single Bond 3M/ESPE) without bevel (butt joint); group 2 beveled direct composite resin restoration; group 3 indirect composite resin inlay (Z250 and Rely X ARC 3M/ESPE) without bevel(butt joint); group 4 beveled indirect composite resin inlay; group 5 sound teeth; group 6 teeth with MOD preparations (no restorations). For the retention test, the incisal edge of 90 lower incisors was sectioned, and divided in the same restorative groups as described above (except group 6). To evaluate gap presence or absence, proximal box cavities were prepared in 24 human third molars, which were restored with direct or indirect composite restorations, with or without bevel, similar to above described and examined under SEM evaluation. Data was statistically analysed by A NOVA, Tukey and t-student tests for fracture strength and retention tests, and Fisher s exact test for gap formation (=0,05). At the 24 hours, beveled restorations exhibited higher fracture strength values than non beveled restorations and most of the tested groups showed resistance similar or superior than sound teeth. After 6 months, the best results were obtained for beveled inlays and the worst values were observed for butt joint direct restorations. In the retention test,beveled restorations had superior performances than non-beveled restorations, in both periods of time. For both tests, a 6-month storage time and thermal cycling produced significant properties decrease in groups 1, 2 and 4 showed. Under SEM examination, no difference was observed among groups after 24 hours. However,after 6 months, beveled restotations remained without gap formation and they had better performance than butt joint restorations. Pearson correlation test showed positive correlation between fracture strength and retention tests. Within the limitations of the study, it was concluded that aging impaired adhesive properties, bevel improved the performance in all tests and generally indirect restorations were not superior to direct restorations.